Synthesis of a Imine vic-Dioxime Ligand and Its Ni(II), Co(II), Cu(II) Complexes - Yenikaya, Cengiz; Kaya, Muharrem; Demir, Ibrahim (Asian Journal of Chemistry, 2010)
A novel imine vic-dioxime compound and its transition metal complexes were synthesized. The compound, N'-hydroxy- 2-(hydroxyimino)-N-(4-(2,4,6-trihydro-xybenzylideneamino)- naphthalen-1-yl)acetimidamide (H2L), has been derived from naphthalene as an imine oxime ligand. The ligand and their complexes were characterized FT-IR, UV, 1H NMR, 13C NMR, MS, elemental analysis and conductometric measurements.